Optimizing the Environment of SMK N 1 Merek: A Study on the Implementation of Waste Bins and Environmental Education Banners - Fachri Dahnial; Rahimah Rahimah (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to optimize the environmental carrying capacity at SMK N 1 Merek through the implementation of waste bins and environmental education banners. The study employs a descriptive approach using observation and interviews to collect data. The findings indicate that the strategic placement of waste bins and informative educational banners significantly enhance students' awareness of environmental cleanliness. Additionally, the behavior of disposing of waste properly has shown a marked improvement. This study concludes that the combination of physical facilities and visual education effectively supports sustainable environmental management within the school environment.